Investigating Priming Effects of Physical Practice on Motor Imagery-Induced Event-Related Desynchronization - Daeglau, Mareike; Zich, Catharina; Emkes, Reiner; Welzel, Julius; Debener, Stefan; Kranczioch, Cornelia (Frontiers in Psychology, 2020)
For motor imagery (MI) to be effective, an internal representation of the to-be-imagined movement may be required. A representation can be achieved through prior motor execution (ME), but the neural correlates of MI that are primed by ME practice are currently unknown. In this study, young healthy adults performed MI practice of an unimanual visuo-motor task (Group MI, n = 19) or ME practice combined with subsequent MI practice (Group ME&MI, n = 18) while EEG was recorded. Data analysis focused on the MI-induced event-related desynchronization (ERD). Specifically, changes in the ERD and movement times (MT) be-tween a short familiarization block of ME (Block pre-ME), conducted before the MI or the ME combined with MI practice phase, and a short block of ME conducted after the practice phase (Block post-ME) were analysed. No priming effects of ME practice on MI-induced ERD were found, nor performance-enhancing effects of MI practice in general. We found enhancements of the ERD and MT in Block post-ME compared to Block pre-ME, but only for Group ME&MI. A comparison of ME performance measures before and after the MI phase indicated however that these changes could not be attributed to the combination of ME and MI practice. The mixed results of this study may be a consequence of the considerable intra- and inter-individual differences in the ERD, introduced by specifics of the experimental setup, in par-ticular the individual and variable task duration, and suggest that task and experimental set-up can affect the interplay of ME and MI.